(untitled) (Bangladesh Journal of Zoology, 2024)
A preliminary study was conducted on craniomandibular measurements in the lesser ricefield rat (Rattus losea) collected from Taiwan, using traditional morphometrics among a total of 26 morphometric characteristics. A relatively larger mean size was detected in males for 18 (69.23%) measurements. The condylobasal length ranged from 35.35 to 40.28 mm (mean: 37.65, SD: ± 1.63) in males and 36.38 to 39.12 mm (mean: 37.50, SD: ± 1.02) in females. The mandibular length varied from 19.62 to 23.95 mm (mean: 21.40, SD: ± 0.32) in males and 20.48–22.08 mm (mean: 21.04, SD: ± 0.52) in females. Two-sample univariate analysis indicated non-significant difference between the sexes for all measurements. In overall measurements, the length of the nasal bone was comparatively longer than the length of the frontal, parietal, and inter-parietal bone. Most characteristics of the skull (72%) showed a significant correlation with condylobasal length. Although the first principal component (PC) accounted for 58.24% of the total variance, scatter plots of the principal components showed that male and female values largely overlapped. Finally, we discussed the morphological characteristics of the R. losea skull in relation to the patterns of other Rattus species. Bangladesh J. Zool. 52(2): 225-235, 2024